Handbook of energy engineering calculations - Hicks, Tyler Gregory, 1921- (New York : McGraw-Hill, 2012)
'This practical guide helps engineers solve energy problems quickly and accurately using step-by-step procedures for performing more than 500 calculations together with worked out examples and numerical results'--Provided by publisher.
Includes index.
Keywords: Power (Mechanics) -- Mathematical models -- Handbooks, manuals, etc; Force and energy -- Mathematical models -- Handbooks, manuals, etc; Engineering mathematics -- Formulae -- Handbooks, manuals, etc